Quasi-cluster randomized trial of a six-month low-intensity group-based resistance exercise for hemodialysis patients on depression and cognitive function: a 12-month follow-up. Issue 1 (1st January 2021) - Nakamura-Taira, Nanako; Horikawa, Naoshi; Oka, Fumie; Igarashi, Yuri; Kobayashi, Sayaka; Kato, Shingo; Enomoto, Takashi; Kimura, Hitomi; Watanabe, Yukari; Kumada, Toru; Matsuyama, Kimihiko; Matsuoka, Naoki; et al.
ABSTRACT: Objective: This study aimed to examine the effects of a six-month group-based low-intensity resistance exercise program on depression and the cognitive function of hemodialysis patients. Method: We conducted a quasi-cluster randomized, open-label controlled study from October 2017 to December 2018. Forty-two patients undergoing hemodialysis completed the trial over six months; half participated in the resistance exercise group ( n = 21, mean = 74.90 years of age, SD = 2.23, 66.67% female) and the other half were in a stretching control group ( n = 21, mean = 72.57 years of age, SD = 2.26, 28.57% female). Depressive symptoms and cognitive function were the primary outcome measures. Behavioral and psychological problems associated with cognitive decline (NPI-Q), subjective insomnia, and exercise self-efficacy were secondary outcomes. Outcomes were measured at baseline, three-month (mid-intervention), six-month (end of intervention), and 12-month (six months after intervention) follow-ups. Linear mixed model analyses were used to determine short-term (immediately after intervention) and long-term (six months after intervention) effects. Results: In depression, cognitive function, and the NPI-Q, there were no significant effects. In subjective insomnia, a short-term group-by-time interaction in the intervention group compared to the control group was found (ES = .43). However, the effect had disappeared by the 12-month follow-up. In exercise self-efficacy, short- and long-term group-by-time interactions were found. A significant short-term increase in the resistance exercise and a significant decrease in the stretching control was observed (ES = -.83). However, the effect was weakened in the long term (ES = -.38). Conclusion: The results showed that low-intensity group resistance exercise would reduce subjective insomnia and improve exercise self-efficacy, but the effect was not maintained by six months after the program. Trial registration: This study was registered on the University Hospital Medical Information Network Clinical Trials Registry (UMIN000029372). Trial registration: UMIN Japan identifier: UMIN000029372.